Akuntabilitas Penyidik dan Prinsip Keadilan: Menimbang Nilai Maqāṣid al-Sharīʿah pada Penetapan Tersangka - Septiawan, Aris; Rifai, Anis; Suartini, Suartini (Tasyri' : Journal of Islamic Law, 2025)
Fair law enforcement requires accountability of investigators in every process of determining suspects. In practice, there are still procedural irregularities that cause legal uncertainty and violations of the human rights of suspects. This research aims to examine the principle of accountability of National Police investigators in determining suspects based on the Criminal Code and police regulations, and to weigh them from the perspective of maqāṣid al-sharīʿah, especially the value of justice ('adl) and the protection of rights (ḥifẓ al-nafs wa al-'ird). This study uses a juridical-normative approach with a descriptive qualitative analysis method, through the study of laws and regulations, pretrial decisions, and Islamic legal literature. The data were analyzed using the framework of maqāṣid al-sharīʿah as an ethical and normative knife. The results of the study show that the determination of suspects without sufficient preliminary evidence violates the principle of due process of law and harms the maqāṣid of justice. Investigator accountability should be realized through internal control mechanisms, ethical sanctions, and judicial supervision through pretrial. The discussion emphasized that the integration of maqāṣid al-sharīʿah values can strengthen the national legal accountability system, as it places justice and the protection of individual rights as the main goals of law enforcement. Therefore, a reconstruction of the maqāṣid-based investigation paradigm is needed to realize humane, ethical, and substantive law enforcement.